(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Key Words: Hot water seed treatment; phomopsis blight of eggplant DOI: 10.3329/bjar.v34i4.5847 Bangladesh J. Agril. Res. 34(4) : 723-727, December 2009